Examining sources of ecological resilience to climate change for restoration planning - Timpane-Padgham, Britta (My University, 2014)
Restoration ecology is a burgeoning field and ecological restoration efforts are becoming more wide-spread. However studies reveal that many restoration efforts fail to accomplish their objectives because they do not address the root cause of degradation or because there is a mismatch between the scale of the problem and scale of the restoration action. Currently, practitioners are faced with the dual challenge to restore system functioning while preparing for unknown impacts from anthropogenic climate change. Climate change could serve as the needed catalyst to shift approaches that allow for natural variability and shifting dynamics to accommodate for unknown climate change impacts. Restoring natural sources of resilience is believed to be an effective way to build adaptive capacity to climate change. There are however many questions surrounding the pragmatic application of resilience theories. One such barrier is identifying what factors within a system influences response to disturbance. Consequently, a critical first step is to identify the dynamic processes and associated attributes that influence resilience in natural systems. In this study, I examined published literature to identify a suite of ecological attributes that influence resilience, either through resisting change or recovering from disturbance. I then developed a Decision Support Tool (DST) to navigate the resilience attributes and to help integrate resilience planning and monitoring into restoration projects.
Thesis (Master's)--University of Washington, 2014
Keywords: climate change; decision support tool; ecological resilience; ecological restoration; recovery; resistance; Environmental management; Ecology; Environmental science; marine affairs